2011
DOI: 10.1177/0267658311405923
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the applicability of Processability Theory: The case of nominal plural

Abstract: This article identifies empirical evidence (Dao, 2007; in preparation) conflicting with Processability Theory's (PT) prediction that in acquisition of English as a second language (ESL), plural-marking emerges first in bare nouns and only later in numeric expressions. Specifically, it presents results from Dao's (2007) cross-sectional study of ESL in 36 Vietnamese learners, which was designed to test PT's predictions that inflections emerge in lexical contexts before agreement in phrasal contexts, but found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…Moreover, there were differences in performance between English‐ and French‐speaking learners on demonstrative‐predicate agreement, which cannot be accounted for by PT. Finally, Charters, Dao, and Jansen () found that number agreement generally emerged in phrasal before lexical contexts (the opposite of the order predicted by PT) in the data from 36 Vietnamese learners of English, although they claim that this pattern can be accounted for by the Developmentally Moderated Transfer Hypothesis (Pienemann, Di Biase, & Kawaguchi, ), which states that L1 transfer of PT processing routines is possible if the L1 processing system is able to process the L2 input directly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there were differences in performance between English‐ and French‐speaking learners on demonstrative‐predicate agreement, which cannot be accounted for by PT. Finally, Charters, Dao, and Jansen () found that number agreement generally emerged in phrasal before lexical contexts (the opposite of the order predicted by PT) in the data from 36 Vietnamese learners of English, although they claim that this pattern can be accounted for by the Developmentally Moderated Transfer Hypothesis (Pienemann, Di Biase, & Kawaguchi, ), which states that L1 transfer of PT processing routines is possible if the L1 processing system is able to process the L2 input directly.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latest PT publications have explicitly hypothesized that the development of syntax and morphology has two separate motivations (Di Biase & Kawaguchi, 2013;Pienemann & Kebler, 2012;Yamaguchi, 2013). In this context, recent cross-sectional and longitudinal studies on English L2 learners have demonstrated the effects of L1 influence and individual variation on morphological development (Charters, Dao, & Jansen, 2011;Dao, 2007;Dyson, 2009;Zhang & Widyastuti, 2010). Meanwhile, other longitudinal child L2 studies have confirmed PT prediction (Yamaguchi, 2013;Yamaguchi & Kawaguchi, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Dao (2007) tested a PT prediction for 36 adolescent Vietnamese-speaking EFL learners (N ¼ 36) using cross-sectional speech data from communicative tasks and found that plural-marking was acquired in a phrasal context with numerically quantified nouns before the emergence of the bare lexical plural against PT prediction, according to Charters et al (2011). With reference to Dao's (2007) findings, Charters et al (2011) conducted a further discussion using a speech processing model called Weaverþþ (Levelt, Roelofs, & Meyer, 1999) and clarified that this counterevidence to L1 transfer was still within range of PT's Developmentally Moderated Transfer Hypothesis that "one can only transfer what can be processed" (Pienemann & Kebler, 2011, p. 75). Zhang and Widyastuti (2010) also empirically revealed L1 transfer in L2 morphological use within the PT framework.…”
Section: Empirical Studies Testing Pt Predictionmentioning
confidence: 99%
See 2 more Smart Citations